We want to derive the quadratic formula from the following expression
![x^2+(b)/(a)x+(b^2)/(4a^2)=-(c)/(a)+(b^2)/(4a^2)](https://img.qammunity.org/2023/formulas/mathematics/college/dil6fplwzt58l7p5opedftbk28me3egue3.png)
The next step would be rewrite the left side of the equation as the square of a sum, and combine the two terms on the right side of the equation on a single fraction.
Let's start by rewriting the left side.
When we expand the square of a binomial, we have
![(m+n)^2=m^2+2mn+n^2](https://img.qammunity.org/2023/formulas/mathematics/college/jm8j9vrji84cmhy4dodiw8yk50ix6wqsid.png)
In our expression, we have
![x^2+(b)/(a)x+(b^2)/(4a^2)=x^2+(b)/(a)x+((b)/(2a))^2](https://img.qammunity.org/2023/formulas/mathematics/college/bx0k8u0g46ydo10cqumegzh6eqxryzo2fm.png)
Comparing our expression with the expansion of a squared binomial, we have
![\begin{cases}m=x \\ n=(b)/(2a)\end{cases}\Rightarrow x^2+(b)/(a)x+((b)/(2a))^2=(x+(b)/(2a))^2](https://img.qammunity.org/2023/formulas/mathematics/college/3lv64yfcb8sqqnxfmcalkm89t0zij50o67.png)
Then, our original expression can be rewritten as
![\begin{gathered} x^2+(b)/(a)x+(b^2)/(4a^2)=-(c)/(a)+(b^2)/(4a^2) \\ (x+(b)/(2a))^2=-(c)/(a)+(b^2)/(4a^2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6yg8kjsoo0jyjdzx3rvpuseg31p9pmshew.png)
And finally, by combining the terms on the right side, we have
![\begin{gathered} (x+(b)/(2a))^2=-(c)/(a)+(b^2)/(4a^2) \\ (x+(b)/(2a))^2=-(c)/(a)\cdot(4a)/(4a)+(b^2)/(4a^2) \\ (x+(b)/(2a))^2=-(4ac)/(4a^2)+(b^2)/(4a^2) \\ (x+(b)/(2a))^2=(-4ac+b^2)/(4a^2) \\ (x+(b)/(2a))^2=\frac{b^2-4ac^{}}{4a^2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g9javpz0ok63tw7ynvymnoql1zkb9anrxm.png)
This is the next step. The answer is option C.